2022
DOI: 10.21533/pen.v10i3.2905
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial and intrapreneurial intentions: Analyzing the premise of distinct constructs with different determinants

Abstract: This study investigates the entrepreneurial and intrapreneurial intentions of the working-age population in Bosnia and Herzegovina by considering a set of demographic and entrepreneurial background factors. Using a cross-sectional survey design, 782 responses were collected. To test hypotheses, confirmatory factor analysis, Welch's t-test, one-way variance analysis with Brown-Forsythe, Welch's F, and least square difference post hoc tests were used. The results suggest several theoretical and practical implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Specifically, the role of age in intrapreneurial literature has primarily been explored in connection with intrapreneurial behavior. The exceptions to this trend include Douglas and Fitzsimmons (2013), who found age statistically insignificant concerning intrapreneurial intention, and Bičo et al (2022), who observed stronger intrapreneurial intention among younger age groups. Furthermore, the mechanism through which age relates to entrepreneurial and intrapreneurial intentions has yet to be sufficiently explored (Fayolle and Linan, 2014).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Specifically, the role of age in intrapreneurial literature has primarily been explored in connection with intrapreneurial behavior. The exceptions to this trend include Douglas and Fitzsimmons (2013), who found age statistically insignificant concerning intrapreneurial intention, and Bičo et al (2022), who observed stronger intrapreneurial intention among younger age groups. Furthermore, the mechanism through which age relates to entrepreneurial and intrapreneurial intentions has yet to be sufficiently explored (Fayolle and Linan, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Thus, the present study also evaluates if older and younger employees possess similar levels of IEO and how that affects their propensity to become intrapreneurs. It is worth noting that although entrepreneurial and intrapreneurial intentions are very closely related concepts, often studied under the umbrella of entrepreneurship, they are distinct constructs (Douglas and Fitzsimmons, 2013; Bičo et al , 2022). However, these two concepts can share common antecedents, while the nature and strength of their relationships to these antecedents may diverge (Bičo et al , 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although EI received significant attention in research, this was not the case with II since there are fewer of these studies available (Bi co et al, 2022). Numerous studies measure intentions through the population and the labor force.…”
Section: Ei II and Labor Forcementioning
confidence: 99%